The Analysis of Relationship Between Digital Transformation, Audit Risk, and Professional Skepticism Towards Audit Quality - Tjia, Callista; Rahayu, Puji Astuti (Jurnal Akuntansi, 2024)
Abstract Purpose - The objective of this study is to examine how audit quality is affected by audit risk, professional skepticism, and digital transformation at Public Accounting Firms (KAP).Design/methodology/approach - 45 auditors were used as study samples. The audit quality dependent variable is the research variable, and the independent variable comprises digital transformation, audit risk, and professional skepticism. Findings - The study's findings revealed digital transformation and professional skepticism affect audit quality. Audit quality, nevertheless, is unaffected by audit risk. Meanwhile, digital transformation, audit risk, and professional skepticism simultaneously affect audit quality.      Research limitations/implications – Only includes a sample of 12 KAP in Indonesia. Most respondents work at KAP big 4. Respondents have not spread evenly. Keywords: Audit Quality, Audit Risk, Digital Transformation, and Professional Skepticism